UMIN Online Abstract and Paper Entry System for Biomedical Academic Meetings - Aoki, N.; Kiuchi, T. (Methods of Information in Medicine, 2007)
Objectives: The object of this research is to develop and evaluate the Online Abstract and Paper Entry System (OAPES) that collects and delivers medical academic meeting information online in Japan.Methods: CGI technology and semi-automated program generation method are employed for the OAPES software development to accommodate the various data collected by many meetings in a common data format and to achieve both flexibility and efficiency.Results: Using OAPES, an abstract, or paper, and its related information can be submitted via the Internet. After contributions have been accepted, bibliographic information is automatically added to the bibliographic information database that is retrievable, free of charge, from the Internet. Since 1997, we have provided OAPES for biomedical academic meetings in Japan. In fiscal 2006, 488 biomedical academic meetings, most of those held in Japan, used OAPES; 106,461 abstracts and papers were handled. To the best of our knowledge, there are no other abstract entry systems in any populous country that are almost monopolistic in a particular major academic field in the way OAPES is. The data format of OAPES and its user interface are now the de facto standard for academic information exchange related to academic meetings in Japan.Conclusions: We succeeded in developing an efficient and prompt online collection and delivery system for medical academic meeting information in Japan and demonstrated that it really works.
Keywords: Medical libraries; internet; online system